Religious icons in Philippine homes a study on the significance of Catholicism in the ornamental design of Filipino interiors - Rivera, Maria Camille F.; Faustino, Johanna Acab. (2007.)
Filipinos are predominantly Catholic and Filipinos express the faith in their own distinctive manner. The purpose of this study was to evaluate the perceptions of Filipino Catholics toward their religion and its manifestations on the ornamentation of the Filipino home and to determine the most common religious items used by Filipinos to decorate their homes and their reasons behind it. The study will aid designers incorporate religion into the design of homes for clients. The study was conducted among 30 Catholic respondents who were household heads and three middle-middle income home-owners residing in Baranggay Poblacion, Makati City. Most present-day Filipino Catholics have a new definition of being religious. Contemporary religiosity is religiosity stripped down to the very basics: faith, action, and display of devotion. Rituals and practices of folk Catholicism are no longer basis for one's level of religiosity. One method of religious exhibition is the putting up of religious items in one's home. Filipinos vary in their perception towards Catholicism in the home. Among these varying perceptions is that religious items although deemed necessary, are not a requirement but just reminders of our faith and that Filipinos are divided on their views whether religious items in the home should be in public or private areas. Based from the results of this study, the researcher was able to conclude that the religion plays an important role in the ornamental design of Filipino interiors and that this role is an underlying factors in reinforcing the family's spiritual stability. All these should be considered when designing Filipino home interiors.
Thesis (BID)--University of the Philippines Diliman.
Keywords: Interior decoration -- Philippines; Idols and images -- Philippines